Pengenalan & Pelatihan Kewirausahaan dengan Membuat Buket Snack untuk Anak Usia Remaja di Panti Asuhan Kasih Ibu Bangkinang - Rahmad Akbar; Dzulhijjah Yetti; Merlia Rahmayani; Harmi Yelmi; Andri Nofiar. Am; Antoni Pribadi; Nurbit Nurbit (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Giving gifts or souvenirs among young people with flower bouquets has become common place, unfortunately the flower bouquets we give often wither and become trash. One alternative substitute for souvenirs or flower bouquet gifts is a snack bouquet. Giving a snack bouquet not only cheap and affordable, it also provides more benefits because we can eat the snacks. The Trend of giving souvenirs or gifts in the form of a bouquet of snacks can be a form of business for young people, especially for the teenagers of the Kasih Ibu Bangkinang Orphanage. After this activity, it is hoped that teenagers can develop an entrepreneurial spirit and will grow into creative individuals. The problem of teenagers at Kasih Ibu Orphanage is that they do not have insight into entrepreneurship and there is a lack of activities that build their creativity and skills. Therefore, training is needed to increase understanding of education about entrepreneurship and a spirit of creativity that is trained at an early age, which is the main capital for their productivity and independence when they grow up. For sustainability programs, because children's entrepreneurship cannot be carried out alone, guidance and support from adults, assistants in orphanages and teachers are needed. Providing opportunities for teenagers to learn to do business (entrepreneurship) from a young age is not oriented towards making money, but rather to train independence, by relying on their creativity.